CIRCULATING MICRORNAS LINKING PRE-ECLAMPSIA WITH FUTURE CARDIOVASCULAR DISEASE. (June 2018) - Schlosser, K.; Pilote, L.; Dayan, N.; Stewart, D.J.; Kaur, A.; Delles, C.
Abstract : Objective: Women with a history of pre-eclampsia (PE) are at increased risk of cardiovascular events later in life. The mechanisms underlying this association are incompletely understood but likely include changes in vascular function and structure. microRNAs (miRs) may play a role in vascular health and disease; therefore, we assessed profiles of circulating miRs in women who had PE, with or without subsequent cardiovascular disease. Design and method: We performed comprehensive profiling of circulating miRs by RNA sequencing (Qiagen, Hilden, Germany) of plasma samples from two independent cohorts: a cohort of women who presented with premature acute coronary syndrome (ACS; cohort 1: n = 18 with and n = 17 without history of PE) and a cohort of women without overt cardiovascular disease (cohort 2: n = 20 with and n = 20 without history of PE). miR profiles associated with history of PE and ACS were established based on fold change > = ± 1.5 and P < 0.05. Targetscan 7.0 was used to predict miR targets and KEGG pathway enrichment was determined with Partek Pathway and Genomics Suite. Results: Women in the two cohorts were on average 48 years of age and had prior pregnancy over 20 years before. A total of 183 and 107 miRs were found to be differentially expressed between cases and controls in cohorts 1 and 2, respectively. Five miRs (hsa-miRs 3131, 346, 4305, 4670–3p and 5698) were concordantly increased or decreased in both cohorts. There were 39 and 29 KEGG pathways significantly (FDR < 0.05) enriched in cohorts 1 and 2, respectively, of which 23 pathways overlapped between the cohorts. Further analysis identified 13 KEGG pathways that were common between all comparisons of PE vs control in cohorts 1 and 2, and ACS vs non-ACS across the cohorts, including cancer, Wnt signalling, TGF-beta and focal adhesion pathways. Conclusions: By analysing circulating miR profiles, we identified pathways that are common between women with ACS and women with history of PE. Of particular importance, pathways involved in cell growth and adhesion may provide explanations for the link between PE and future cardiovascular diseases.